Sleep quality of patients with heart failure and associated factors - Juliana Pessoa de Souza; Danielly Farias Santos de Lima; Oriana Deyze Correia Paiva Leadebal; Maria Eliane Moreira Freire; Simone Helena dos Santos Oliveira; Vinicius Batista Santos; Mailson Marques de Sousa (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to assess sleep quality of patients with heart failure and associated sociodemographic and clinical characteristics. Methods: a cross-sectional study, developed with 88 patients. Sleep quality was assessed by the Pittsburgh Sleep Quality Index. The data were analyzed using descriptive and inferential statistics. Results: the mean sleep quality score was 8.59 ± 3.60 points. 83% of participants were classified as poor sleepers. The number of hours of sleep was 5.99 ± 1.48. Family income of up to one minimum wage and functional class were significantly associated with poor sleepers. There was a positive correlation between functional class and poor sleep quality. Conclusions: a high frequency of poor sleepers was identified. Worse scores were associated with family income and symptomatic functional class. Health interventions are necessary to control sleep quality, especially in relation to health functionality.